Cardiomyopathy in limb girdle muscular dystrophy R9, FKRP related. Issue 5 (10th September 2020) - Libell, Eric M.; Richardson, Julia A.; Lutz, Katie L.; Ng, Benton Y.; Mockler, Shelley R. H.; Laubscher, Katie M.; Stephan, Carrie M.; Zimmerman, Bridget M.; Edens, Erik R.; Reinking, Benjamin E.; Mathews, Katherine D.
Abstract: Introduction: Reported frequencies of cardiomyopathy in limb girdle muscular dystrophy R9 (LGMDR9) vary. We describe the frequency and age at onset of cardiomyopathy in an LDMDR9 cohort. Methods: Echocardiograms from 56 subjects (157 echocardiograms) with LGMDR9 were retrospectively reviewed. The cumulative probability of having an abnormal echocardiogram as a function of age was assessed by survival analysis for interval‐censored data by genotype. Correlations between cardiac and clinical function were evaluated. Results: Twenty‐five (45%) participants had cardiomyopathy. The median age at first abnormal echocardiogram for subjects homozygous for the c.826C>A variant was 54.2 y compared to 18.1 y for all other fukutin‐related protein ( FKRP ) genotypes ( P < .0001). There was a weak correlation between ejection fraction and 10‐Meter Walk Test speed (r = 0.25), but no correlation with forced vital capacity (r = 0.08). Discussion: Cardiomyopathy is prevalent among those with LGMDR9 and occurs later in subjects homozygous for the c.826C>A mutation. These data will help to guide surveillance and management.